Kajian Karakter Kepemimpinan Oda Nobunaga Dalam Novel Shinsho Taikōki Karya Eiji Yoshikawa Dengan Pendekatan Teori Praktik Bourdieu - Silvi Mega Suri; Haryono Haryono; Yudi Suryadi (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2020)
This research analyzes the character of Oda Nobunaga's leadership from his social side. The purpose of writing this essay is to describe habitations, arenas and capital, and the third correlation which deforms the leadership character of Oda Nobunaga. In writing this essay used a book study method. The technical analysis of the data used is a descriptive analysis. The conclusion of this study has been found that (1) the Shinsho Taikōki pictures the form of one's habitation in determining action. Natural changes in agents continue to move around as time goes on. The movement is a result of his experience, upbringing, and environment; (2) there are three arenas in the Shinsho Taikōki, which is the power arena, the economic arena and the intellectual arena. These three arenas stand out from two factors, among them because of the dominant class, and where that agent's capital was obtained; (3) the capital found in the agent of this novel has three, which are social, symbolic and cultural capital. (4) the leadership character of the three social concepts consists of seven characters: Flexibility, ability to determine scale of priorities, analytic capabilities, future orientation, firmness, and exemplary.